Anatomia topográfica e comportamento arterial do pâncreas em cágados Trachemys scripta elegans (wied, 1838) - Vieira, André N. Le Sueur [UNESP]; Melo, Alan Peres Ferraz de; Souza, Wilson Machado de [UNESP]; Rodrigues, Rosângela Felipe (My University, 2013)
The turtle Trachemys scripta elegans popularly known as American tiger water are native regions winged Florida and Mississippi, in the United States. We used twenty (20) turtles (Trachemys scripta elegans), adult males and females, which were euthanized under Resolution 714 of June 20, 2002 the Federal Council of Veterinary Medicine (CFMV). After euthanasia were identified aortas right and left to the injection of Neoprene latex 450, stained with specific pigment. To obtain the vinyl mold aorta was injected through the right and left vinyl acetate, followed by corrosion in sulfuric acid. It was observed that the pancreas is closely related to the liver, gizzard, gall bladder, and duodenum. His face cranial this distal region of the pylorus, while its caudal along the cranial region of the duodenum. Anatomically, the pancreas is an elongated body structure featuring a lightly lobed. As to the pancreas arterial vasculature is flushed in its transverse plane of two arteries arising from the celiac artery, and each antimere two pancreaticoduodenal artery in the cranial region, close to the pylorus by the pancreaticoduodenal artery flow in the caudal portion along the duodenum.

O cágado Trachemys scripta elegans conhecido popularmente como "tigre d´água americano" são espécies nativas das regiões aladas da Flórida e do Mississipi, nos Estados Unidos. Foram utilizados 20 (vinte) cágados (Trachemys scripta elegans), machos e fêmeas adultos, os quais foram eutanasiados segundo a Resolução 714 de 20 de junho de 2002 do Conselho Federal de Medicina Veterinária (CFMV). Após a eutanásia foram identificados as aortas direita e esquerda para a injeção de Neoprene látex 450, corado com pigmento específico. Para a obtenção do molde de vinil foi injetado através das aortas direita e esquerda o acetato de vinila, seguido por corrosão em ácido sulfúrico. Observou-se que o pâncreas está intimamente relacionado com o fígado, ventrículo gástrico, duodeno e vesícula biliar. Sua face cranial esta na região distal do piloro, enquanto sua porção caudal ao longo da região cranial do duodeno. Anatomicamente o pâncreas é um órgão de estrutura alongada apresentando uma superfície levemente lobada. Quanto à vascularização arterial o pâncreas é irrigado em seu plano transversal por duas arteriais oriundas da artéria celíaca, e em cada antímero por duas artérias pancreaticoduodenais na região cranial, próximo ao piloro, pela artéria pancreaticoduodenal cranial e na porção caudal, ao longo do duodeno, irrigado pela artéria pancreaticoduodenal caudal.
Anatomy surveying and behavior in pancreatic blood tortoises Trachemys scripta elegans (wied, 1838)
Keywords: Morphology; Pancreas; Tortoises; Trachemys scripta elegans